Internal Control, Audit Quality, and Tax Avoidance: Evidence from Property and Real Estates - Fransisco Pandapotan; Fitria Puspitasari; Alfina Maharani (International Publisher (YAPENBI), 2023)
Even though taxpayers are given a trust to calculate, pay, and report their taxations to the government under self-assessment system, the practice of tax avoidance is still high. Comparing to tax evasion, tax avoidance is a practice that is legally done by management in order to pay minimum taxes. However, this is in contrast with the government that wants maximum payment of taxes from taxpayers. This research is conducted to see the factors affecting tax avoidance. Those determinants are internal control and audit quality. The population of this research is property and real estate companies which are listed in Indonesia Stock Exchange period 2020 and 2021 with a purposive sampling technique, so that there are 48 samples used. According to the results of multiple linear regression by SPSS 22, the findings of this research are internal control and audit quality have negative and significant effects on tax avoidance